Analysis of the overall structure of the multi-domain amyloid precursor protein (APP). - Ina Coburger; Sven O Dahms; Dirk Roeser; Karl-Heinz Gührs; Peter Hortschansky; Manuel E Than (PLoS ONE, 2013)
The amyloid precursor protein (APP) and its processing by the α-, β- and γ-secretases is widely believed to play a central role during the development of Alzheimer´s disease. The three-dimensional structure of the entire protein, its physiologic function and the regulation of its proteolytic processing remain, however, largely unclear to date. To gain a deeper understanding of the structure of APP that underlies all of its functions, we first cloned and recombinantly expressed different constructs in E. coli. Using limited proteolysis followed by mass spectrometry and Edman degradation as well as analytical gel permeation chromatography coupled static light scattering, we experimentally analyzed the structural domain boundaries and determined that the large ectodomain of APP consists of exactly two rigidly folded domains - the E1-domain (Leu18-Ala190) and the E2-domain (Ser295-Asp500). Both, the acidic domain (AcD) connecting E1 and E2 as well as the juxtamembrane region (JMR) connecting E2 to the single transmembrane helix are highly flexible and extended. We identified in-between the E1-domain and the AcD an additional domain of conservation and partial flexibility that we termed extension domain (ED, Glu191-Glu227). Using Bio-layer interferometry, pull-down assays and analytical gel filtration experiments we demonstrated that the E1-domain does not tightly interact with the E2-domain, both in the presence and in the absence of heparin. APP hence forms an extended molecule that is flexibly tethered to the membrane. Its multi-domain architecture enables together with the many known functionalities the concomitant performance of several, independent functions, which might be regulated by cellular, compartment specific pH-changes.